Experimental evaluation of Napier grass gasification in an autothermal bubbling fluidized bed reactor - Khezri, Ramin; Wan Ab. Karim Ghani, Wan Azlina; Awang Biak, Dayang Radiah; Yunus, Robiah; Silas, Kiman (MDPI, 2019)
Air gasification of Napier grass (NG) was studied with the target of producing combustible synthesis gas to be used in direct combustion for power generation. A small-scale autothermal bubbling fluidized bed gasifier was used to investigate the effect of reactor temperature, equivalence ratio (ER), and static bed height (SBH) on gasification performance and combustibility of the producer gas. The main generated species in syngas were identified through gas chromatography (GC) analysis. Minimum fluidization conditions were determined at different levels of SBH. Experiments carried out with two intentions of first, to achieve the highest composition of combustible species to ensure the maximum Lower Heating Value (LHV) of syngas and second, to obtain a high performance process with maximum yield of syngas and minimum residues. The results showed that the temperature and ER have significant effects on syngas yield and composition. SBH was found have a substantial effect on the production of H2 and CO. The results from this study was compared to other gasification studies from literature which have evaluated biomass gasification in bubbling fluidized bed reactors with different scales but almost similar method of experimentation. The purpose of verification was to demonstrate the effect of different reactor scales and heating characteristics on the results.